Quality Analysis of the Product - A., Tovma N.; H, Hajek P. (Farabi Journal of Social Sciences, 2019)
Abstract. In this article, the analysis of the quality of the product is presented and new approaches based on the indices methods for the product quality are considered. Quality includes various components. The main of them are technical and economic indicators of the product quality as well as quality of production technology and capacities. Furthermore, indicators of reliability, durability, labor, capital and research intensity are also in this list.